Validation of HPLC for identification of captopril, enalapril, and lisinopril in traditional Indonesian herbal medicine - Liliek Nurhidayati; Mawarni Tobing; Elvi Rahmayuni (Faculty of Pharmacy, Universitas Pancasila, 2026)
Traditional Indonesian herbal medicine (Jamu) is widely used for health maintenance and disease prevention. The addition of medicinal chemicals to Jamu is not in accordance with quality and safety requirements. The purpose of this study was to develop a valid HPLC method for the identification of captopril, lisinopril, and enalapril in Jamu for hypertension. In this study, they were identified using high-performance liquid chromatography with a photodiode array detector. The stationary phase was a C18 YMC column (length 250 mm, diameter 4.6 mm, particle size 5 μm), methanol - 0.1 % phosphoric acid (45:55) as the mobile phase with isocratic elution, a flow rate of 1.0 mL/min, a column temperature of 40 °C, an injection volume of 20 μL, and detection at 210 nm. The results showed that this method fulfilled the specificity requirement, with detection limits of captopril, enalapril, and lisinopril of 0.715, 0.795, and 1.403 ppm, respectively. This HPLC method can be used for the identification of captopril, enalapril, and lisinopril in commercial Jamu.